2018
DOI: 10.1007/s10637-017-0552-y
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor chidamide induces growth inhibition and apoptosis in NK/T lymphoma cells through ATM-Chk2-p53-p21 signalling pathway

Abstract: We investigated the anti-tumour effects and the underlying molecular mechanisms of a new oral histone deacetylase inhibitor (HDACi), chidamide, in NK/T cell lymphoma (NKTCL), a rare and highly aggressive non-Hodgkin lymphoma with poor outcomes. SNT-8 and SNK-10 NKTCL cell lines were exposed to different concentrations of chidamide for the indicated time. The treated cells were analysed for cell proliferation, cell cycle progression, and cell apoptosis. Proteins in the AKT/mTOR and MAPK signalling pathways and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…A study investigated the antitumour effects and the underlying molecular mechanisms of chidamide and showed that chidamide inhibited cell proliferation and arrested cell cycle progression at the G0/G1 phase. In addition, chidamide suppressed the phosphorylation levels of proteins in the AKT/mTOR and MAPK signalling pathways and activated the DDR cell cycle checkpoint pathway (the ATM-Chk2-p53-p21 pathway) in lymphoma [ 53 ]. Chidamide is now part of many preclinical and clinical trials in lymphoma patients.…”
Section: Epigenetic Drugs In Relapsed and Refractory Ptclmentioning
confidence: 99%
“…A study investigated the antitumour effects and the underlying molecular mechanisms of chidamide and showed that chidamide inhibited cell proliferation and arrested cell cycle progression at the G0/G1 phase. In addition, chidamide suppressed the phosphorylation levels of proteins in the AKT/mTOR and MAPK signalling pathways and activated the DDR cell cycle checkpoint pathway (the ATM-Chk2-p53-p21 pathway) in lymphoma [ 53 ]. Chidamide is now part of many preclinical and clinical trials in lymphoma patients.…”
Section: Epigenetic Drugs In Relapsed and Refractory Ptclmentioning
confidence: 99%
“… 22 A few in vitro experiments demonstrated chidamide induced tumor cells growth arrest and apoptosis through various pathways in NK/T-cell lymphoma cell lines and human leukemia cells. 23 , 24 There are two ex vivo assays provided evidence that chidamide in the appropriate dose enhanced CD8+ CTL and NK cell-mediated cytotoxicity. 21 , 25 Furthermore, chidamide could enhance the anti-tumor activity of PD-1 (+) cells including T cells and B cells.…”
Section: Discussionmentioning
confidence: 99%
“…CM induces anti-tumor effects through various mechanisms, depending on the type of cancer and its dose. These mechanisms include: i) Cell cycle arrest, CM arrests tumor cells at the G 0 /G 1 phase (12,16,25); ii) apoptosis induction, CM induces apoptosis by regulating the balance of pro- and anti-apoptotic genes, activating intrinsic apoptotic pathways (25); iii) suppression of cellular signaling pathways, CM inhibits the Janus kinase/STAT, PI3K/AKT and mitogen-activated protein kinase/JNK signaling pathways (16,19,26,27); iv) reactive oxygen species generation and induction of DNA damage (10,25); v) energy metabolism modulation, CM suppresses mitochondrial aerobic respiration by downregulation of mcl-1 (20); vi) activation of cellular antitumor immunity mediated by NK cells and antigen-specific cluster of differentiation 8-positive cytotoxic T lymphocytes (11); vii) reversion of transforming growth factor-β-induced epithelial-mesenchymal transition in tumor cells (28); and viii) upregulation of the tumor suppressor genes Spi-1 proto-oncogene and Krüppel-like factor-4 (29). In the present study, it was demonstrated that CM serves a role in suppressing the viability of MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chidamide (CM), a novel benzamide type HDACI, selectively suppresses the activity of class I HDACs, including HDAC1, HDAC2, HDAC3 and HDAC10 (10,11). Previous studies have revealed that CM induces cell proliferation inhibition and apoptosis in several hematological malignancies, including myelodysplastic syndromes (12), leukemia (1315) and natural killer (NK)/T-cell lymphoma (16), as well as non-hematological malignancies, including lung cancer (17), hepatocellular carcinoma (18), colon cancer (19) and pancreatic cancer (20). CM was approved by the China FDA for the treatment of peripheral T-cell lymphoma (PTCL) in 2014 (21).…”
Section: Introductionmentioning
confidence: 99%